Perceptions and Practice of Early Diagnosis of Sickle Cell Disease by Parents and Physicians in a Southwestern State of Nigeria - Oladele Simeon Olatunya; Adefunke Olarinre Babatola; Ezra Olatunde Ogundare; Babatunde Ajayi Olofinbiyi; Olubunmi Adeola Lawal; Jacob Olumuyiwa Awoleke; Olusola Peter Aduloju; Alaba Olanrewaju Daramola; Eyitayo Ebenezer Emmanuel; Oyebanji Anthony Olajuyin; Akinwumi Kolawole Komolafe; Abiola Olukayode Olaleye (The Scientific World Journal)
Background. Early sickle cell disease (SCD) diagnosis has shown promise in combating SCD in many countries. The aim of this study was to assess the practice and perception of early SCD diagnosis among a group of parents and physicians in Nigeria. Patients and Methods. This was a cross-sectional descriptive study conducted to assess the opinions and practice of early diagnosis of SCD among 135 physicians caring for SCD patients and 164 mothers of children with SCD in a southwestern state of Nigeria. Results. Most physicians 132 (97.8%) were aware of prenatal SCD diagnosis, but only 51 (37.8%) would recommend it. Most physicians 129 (95.6%) routinely recommend premarital SCD genetic counseling and testing, and 89 (65.1%) were aware of the national government newborn screening program but lesser proportion 75 (55.6%) were willing to recommend it. Amongst the mothers, 154 (94%) and 158 (96%) had encountered genetic counseling for SCD and were willing to offer newborn screening to their children, respectively. On the contrary, fewer mothers 42 (25%) were aware of prenatal SCD diagnosis, 28 (17%) were willing to partake in it, and 44 (26%) were undecided. There were discrepancies in the willingness by physicians to practice early SCD diagnosis and its uptake by mothers (p<0.0001). The commonest reason given by both the physicians and mothers for not practicing SCD prenatal diagnosis was the high cost of the procedure. Conclusion. The perceptions and practice of early SCD diagnosis was suboptimal in the study locality. Scaling up awareness and universal coverage are required.